Nanotechnology for environmental decontamination - Ram, Manoj Kumar; Andreescu, Silvana; Ding, Hanming (McGraw-Hill's AccessEngineering., 2013)
"Written by a team of global experts, Nanotechnology for Environmental Contamination covers the latest methods for using nanomaterials, processes, and tools to remediate toxin-contaminated water, air, soil, groundwater, and wastewater. This groundbreaking work discusses the use of nanotechnology to neutralize microbes, pesticides, heavy metals, industrial chemicals, chemical and biological warfare agents, and other toxic substances. In-depth details on the physics, chemistry, and technology of nanomaterials, nanostructures, and nanotechnology for decontamination are included in this authoritative resource.".